Characterization of exopolysaccharides from probiotic Lactobacillus strains isolated from traditional Malaysian foods - Suliman, Eilaf Suliman Khalil (2018)
Lactic acid bacteria (LAB) are generally recognized as safe (GRAS) microorganisms, and play an important role in food and animal feed as potential probiotics. LAB are used for the production of several industrially interesting metabolites such as bioactive peptides, antibacterial compounds, aroma compounds, and cells wall component like exopolysaccharides (EPS). EPS are generally related to all forms of polysaccharides that are present outside of the microbial cell wall. Although, EPS produced by LAB have multifunctional, technological, and health benefits, their industrial applications are hindered by their low yield. The present study was conducted to isolate and identify varieties of LAB from some traditional Malaysian foods and to investigate their probiotic characteristics, functional properties, ability to produce EPS, and to study their bioactivities. One hundred and twenty LAB strains were isolated from five different traditional Malaysian foods. The preliminary selection carried out optically by screening the strains’ resistance to low pH 2.0 and bile salts 0.3% as well as ability to produce EPS, and a total of 13 isolates were accordingly selected. The 13 isolates were identified using the carbohydrates fermentation profile and 16S rRNA gene sequences. Six of the Lactobacillus strains were associated with the species Lb. fermentum (DUR18, TAP1, PIC7, BU11, BU14, and TAP16) and four strains belonged to Lb. plantarum (DUR2, DUR5, DUR8, and TEMP9). Besides, Lb. crispatus (DUR4) Lb. reuteri (DUR12) and Lb. pentosus (DUR20) were also identified. Two commercial Lactobacillus strains namely: Lb. rhamnosus (ATCC53103) and Lb. plantarum (ATCC8014) were used as reference strains. The isolated strains exhibited high tolerance to acid (<80%) and bile (<65 %) as well as high survival rate in the gastrointestinal tract. The results of the cells wall properties showed that auto-aggregation and cell surface hydrophobicity were ranged between 53-80 and 16-80%, respectively, whereas, the highest co-aggregation value (66%) was reported by Lb. plantarum (DUR8) with Pseudomonas aeruginosa. The in vitro assay for the functional properties of the isolated strains showed antioxidant activity equivalent to trolox (30-70%), high cholesterol assimilated. Also, the isolated strains exhibited good inhibitory activity against some tested pathogens due to organic acids production. The EPS production by the 13 Lactobacillus isolated strains were ranged between 50 and 850 mg/L. Based on that, two strains; Lb. pentosus and Lb. reuteri which showed the highest EPS yield were screened out for further characterization. The purified EPS were composed of glucose, arabinose, and rhamnose. FTIR analysis indicated a specific spectrum of neutral polysaccharides in the region of 1577 cm−1 which attributed to C=O stretching. An extracellular glucosytransferase (GTF) enzyme corresponding to EPS from the selected strains were produced with the molecular weight falls between 120 and 150 kDa. The GTF exhibited high activity under static condition at pH 5 and incubation temperature 28°C. EPS yield from Lb. reuteri and Lb. pentosus were optimized using response surface methodology (RSM). The maximum EPS yields attained were 1.0 g/L and 1.07 g/L produced by Lb. reuteri and Lb. pentosus, respectively. Moreover, the optimal values for the tested variables were: 41 and 39.5 °C for incubation temperature, pH 6.4 and 6.5, and the incubation times were 33.7 and 48 h for Lb. reuteri and Lb. pentosus, respectively. The RSM displayed a significant (p < 0.05) response fit for the studied variables with a high coefficient of determination (R2). The predicted and observed values displayed no significant (p > 0.05) differences. Both incubation time and the pH significantly (p < 0.05) affected the EPS production in both strains. The optimum points were practically validated. The EPS samples revealed potent antioxidant activity to scavenging DPPH (65.8 and 68.0% for Lb. pentosus and Lb. reuteri, respectively) and antibiofilm activity against some pathogens (above 50%). It can be concluded that Lactobacillus strains isolated from traditional Malaysian foods in this study are promising probiotics which have the potential to produce EPS with functional attributes.